Parenting Style, Social Support, Peer Relationship, and Coping Strategies among Students During Online Learning - Oktaviani, Maya; Elmanora; Hasanah, Uswatun (Journal of Family Sciences, 2023)
Covid-19 has significantly impacted the daily lives of all people, so the government needs to take public health measures such as distance and online learning, which makes students adapt to solving problems through coping strategies. This study analyses the influence of parenting style, social support, and peer relationships on students' online learning coping strategies. This study uses an associative quantitative approach. The population in this study were students at the Universitas Negeri Jakarta (UNJ). This study involved 505 students at the Universitas Negeri Jakarta with a voluntary sampling technique. The researcher conducted this study at Universitas Negeri Jakarta from April to June 2023. The researcher analyses the research data using descriptive and inferential statistics, including multiple linear regression tests. The regression test results show that parenting style, social support, and peer relationships can improve student coping strategies. As much as 34.7 percent of adaptability in adjusting or solving student problems can be explained through parenting style, social support, and peer relationships. This research implies that parents and peers contribute significantly to students' coping strategies. Both have their respective roles that can increase or decrease a student's ability to adapt to the problems they face.